Lateral knee snapping in an elite judo athlete: `Sono-Acrobatics` of the popliteus tendon - Karanfil, Y.; Aksöz, B.; Özçakar, L. (Scandinavian Journal of Medicine & Science in Sports, 2024)
A 20-year-old elite judo athlete was seen for snapping at her left knee for the last two years. Herewith, she had increased concern after a recent contralateral anterior cruciate ligament (ACL) reconstruction five months ago. She had no history of trauma to her left knee that would impede participation in training or competition. Radiographs were normal, magnetic resonance imaging (MRI) showed only slight effusion between the popliteal tendon and the lateral femoral condyle. The medical history was otherwise noncontributory.